ESG in private equity and other alternative asset classes: What the industry has accomplished so far regarding environmental, social and governance matters - Jens Hoellermann (European Institute for Knowledge & Value Management (EIKV), 2020)
Over the last years, the rise of sustainability and responsibility has drawn considerable attention by the entire society including businesses. Companies have integrated corporate social responsibility into their business model as a kind of self-regulation, and the way businesses invest has led to socially responsible investing, but it is nowadays accepted that environmental, social, and governance matters cover all the sustainability and responsibility topics and what exactly shall be focused on. This applies to the financial sector and the alternative industry as well, which includes Private Equity, Real Estate, Infrastructure, Private Debt, and Venture Capital. The research question is therefore what Private Equity and other alternative asset classes have accomplished so far in relation to environmental, social, and governance matters, what they say and what they really do, what they have in fact implemented, and what differences between the actors do exist. This topic has to date not been addressed entirely or solved by academia and research. Hence, in total 117 firms have been researched representing 76,2% of the world's total alternative assets. In order to analyze the research question initially the growing demand for sustainability and responsibility will be shown followed by an analysis how environmental, social, and governance has emerged. [...]
Keywords: 650; Sustainability; Responsibility; Corporate Social Responsibility; Socially Responsible Investing; Environmental Social and Governance; Private Equity; Real Estate; Infrastructure; Private Debt; Venture Capital